2016
DOI: 10.18632/oncotarget.7983
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandin vivoanti-tumor activity of CoQ0 against melanoma cells: inhibition of metastasis and induction of cell-cycle arrest and apoptosis through modulation of Wnt/β-catenin signaling pathways

Abstract: Coenzyme Q0 (CoQ0, 2,3-dimethoxy-5-methyl-1,4-benzoquinone), a novel quinone derivative, has been shown to modulate cellular redox balance. However, effect of this compound on melanoma remains unclear. This study examined the in vitro or in vivo anti-tumor, apoptosis, and anti-metastasis activities of CoQ0 (0-20 μM) through inhibition of Wnt/β-catenin signaling pathway. CoQ0 exhibits a significant cytotoxic effect on melanoma cell lines (B16F10, B16F1, and A2058), while causing little toxicity toward normal (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…Sp1-4 factors may play a role in activating some signaling pathways and receptors and contribute to oncogenic properties of cancer cells [13]. Attenuation of Wnt/β-catenin signaling resulted in inhibition of survivin expression in several cell types, suggesting a positive regulation of survivin expression by this pathway in the tested cell lines [14,15]. Herceptin inhibited survivin expression through the ErbB2-β-catenin/TCF4 pathway in breast cancer cells, completely dependent on TCF-4 binding sites in the promoter [16].…”
Section: Positive Regulation Of Survivin Expresssionmentioning
confidence: 99%
“…Sp1-4 factors may play a role in activating some signaling pathways and receptors and contribute to oncogenic properties of cancer cells [13]. Attenuation of Wnt/β-catenin signaling resulted in inhibition of survivin expression in several cell types, suggesting a positive regulation of survivin expression by this pathway in the tested cell lines [14,15]. Herceptin inhibited survivin expression through the ErbB2-β-catenin/TCF4 pathway in breast cancer cells, completely dependent on TCF-4 binding sites in the promoter [16].…”
Section: Positive Regulation Of Survivin Expresssionmentioning
confidence: 99%
“…Previous studies have shown that inhibition of the Wnt/β-catenin signaling pathway attenuates survival signals and induces apoptosis (15,16). Autophagy is a highly conserved pathway that is activated under stress and plays a pivotal role in a plethora of physiological processes including cell death (17).…”
Section: Introductionmentioning
confidence: 99%
“…Membranes were incubated with the following desired primary antibodies: matrix metalloproteinase (MMP)-9 (1: 1,000, catalog no. sc-6840, Santa Cruz Biotechnology) (7,14,31), p-AKT (1:1,000, catalog no. 4085L, Cell Signaling) (17,18,50), AKT (1:1,000, catalog no.…”
Section: Methodsmentioning
confidence: 99%